Plus Trees Selection and their Progeny Evaluation in Prosopis juliflora - Goel, V. L.; Dogra, P. D.; Behl, H. M. (Indian Forester, 1997)
Plus tree selections were made from a 5-yr-old productivity trial of Prosopisjuliflora established on alkaline soil site. Twenty one plus trees were selected on the basis of phenotypic superiority in growth, tree form and disease resistance Minimum selection standard in terms of superiority percentage was 20% for height and 35% for diameter. Single half-sib progeny test of selected plus trees along with control was laid in nursery. Six families outperformed the rest as well as control both in respect to their height and collar diameter. Out of the six, three outstanding single tree progenies examined in field trial along with a check lot showed adaptive growth different among and within progenies. All the selected families outperformed the base population as well as the check lot. The study revealed that considerable gains can be achieved in P.juliflora if elite genotypes are selected, multiplied and used in afforestation programmes.